2019
DOI: 10.1016/j.engstruct.2018.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Current, wave, wind and interaction induced dynamic response of a 5 MW spar-type offshore direct-drive wind turbine

Abstract: This paper studies the dynamic response of a spar-type direct-drive wind turbine subjected to external and internal excitations. A free-free end model is developed for the wind turbine structure with a spar-type floating platform under deep sea condition. Firstly, the spar supported platform with tower structure is modelled as a rigid body while the nacelle is considered as a point mass attached on the top of the tower. Then the dynamic interaction between the drivetrain system and the tower is considered by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 27 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…In the recent decade, the fatigue behavior of construction materials received great attention because natural or human activity-induced loads on buildings are often cyclic in essence [ 11 ]. When concrete is subjected to cyclic loading, there will be residual strain accumulating after each cycle, which indicates the internal progressive permanent structural change in concrete [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decade, the fatigue behavior of construction materials received great attention because natural or human activity-induced loads on buildings are often cyclic in essence [ 11 ]. When concrete is subjected to cyclic loading, there will be residual strain accumulating after each cycle, which indicates the internal progressive permanent structural change in concrete [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been published on offshore wind turbine systems. As representative instances, certain sequential studies have been performed for spar-type offshore wind turbine systems [39][40][41]. First, the natural frequency of a wind turbine tower with end-mass components was investigated [39].…”
Section: Comprehensive Discussionmentioning
confidence: 99%
“…It also generates drag forces on the submerged parts of offshore structures. For a large offshore structure such as articulated tower, current load can be an important source of hydrodynamic damping in few cases as studied by Ye and Ji (2019). Ocean currents are a complex component varying with water depth, time, global location, and so on.…”
Section: Mathematical Modeling and Analysismentioning
confidence: 99%
“…Stochastic response of a tension leg platform (TLP) under random wave and current loads was investigated by Oyejobi et al (2016). In a recent paper, Ye and Ji (2019) investigation of current-, wave-, and wind-induced dynamic response of a 5-MW spar-type offshore wind turbine under high, low, and moderate sea states was performed. Coupled response of floating wind turbine by frequency domain approach was presented by Kunpeng et al (2016) who concluded that the influence of aero-hydro-structure coupling should be considered to get reliable analysis results, during the design of offshore towers.…”
Section: Introductionmentioning
confidence: 99%